Studi Kebutuhan Ruang pada Pengembangan Pelabuhan Penyeberangan Ferry di Kabupaten Kolaka - Aldi Febriansyah Aldi; Haryanto Andi Halim; Aris Alimuddin (Universitas Medan Area, 2026)
Ports as a maritime transportation infrastructure have a very important and strategic role for industrial and trade growth and are a business segment that can contribute to the economy and national development because they are part of the chain of transportation and logistics systems in Kolaka Regency. However, the facilities and infrastructure at the Ferry Ferry Port in Kolaka Regency are still minimal and still have many shortcomings. This study aims to design the development of a ferry ferry port that is able to accommodate the needs of managers, a place for service activities, a place for ships to dock, anchor, embark and disembark passengers or load and unload goods equipped with shipping safety facilities and port supporting activities as well as a place for intra and intermodal transportation transfers, as well as designing the physical structure of the Ferry Ferry Port in Kolaka Regency.